Advanced Heat Sink Integration Strategies for Monocrystalline Solar Panel Performance Enhancement - M. Akmal Ma'arif; Levin Halim; Christian Fredy Naa (International Journal of Integrated Engineering, 2025)
Renewable energy is an alternative solution to solve the problem of global warming. One of the ways to help these problems is to take advantage of solar energy. Solar panels are tools that can transform solar energy into electrical energy. However, solar panels have efficiency sensitivity. In several previous studies, heat sinks can increase the efficiency of solar panels. Therefore, this research is conducted to determine the increase in the efficiency of monocrystalline solar panels using a heat sink. This study uses solar panels of monocrystalline type with the MS50M-18 series. Data collection is carried out with a data logger system using a digital multimeter and Arduino as the direct way, taking at most 140 data every 15 seconds. This study concludes that there is an increased efficiency of solar panels using a heat sink from 8.8% to 11.89% on radiation 700 W/m2 where the maximum temperature is from 77 ?C to 72 ?C when using a heat sink. These findings demonstrate the effectiveness of passive cooling using heat sinks, contributing to optimizing solar panel performance in moderate irradiance conditions. The proposed system offers a low-cost and scalable solution for improving solar energy generation in various environmental settings.